2005
DOI: 10.1039/b414059a
|View full text |Cite
|
Sign up to set email alerts
|

Oriented assembly of Au nanorods using biorecognition system

Abstract: The design and formation of a linear assembly of gold nanorods using a biomolecular recognition system are described. Anti-mouse IgG was immobilized on the {111} end faces of gold nanorods through a thioctic acid containing a terminal carboxyl group. The biofunctionalized nanorods can be assembled with the desired length using mouse IgG for biorecognition and binding. The gold nanorods can be assembled to extended nanorod chains, which can be as long as 3 microm. These assembled nanostructures may be used as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
156
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(165 citation statements)
references
References 16 publications
8
156
0
1
Order By: Relevance
“…It is consistent with the previous reports that the longitudinal band of GNRs is more sensitive to the local environment around GNRs than the transverse band [42][43][44][45]. This result suggested that the aggregation of GNRs takes place in a side-by-side manner [46,47].…”
Section: +supporting
confidence: 82%
“…It is consistent with the previous reports that the longitudinal band of GNRs is more sensitive to the local environment around GNRs than the transverse band [42][43][44][45]. This result suggested that the aggregation of GNRs takes place in a side-by-side manner [46,47].…”
Section: +supporting
confidence: 82%
“…Since θ is not singular at the critical line, we can assume that the singular part of the free energy will make no contribution to Eq. (34) and therefore the derivative of the second term in the right hand of the previous expression vanishes when n → ∞. Therefore, we can express…”
Section: Rsrg Coverage Calculationmentioning
confidence: 99%
“…Selectively functionalizing the ends of hydrophilic nanorods with hydrophobic polymers, Nie et al reported the observation of rings, bundles, chains, and bundled chains [33]. In another experimental study carried out by Chang et al [34], gold nanorods were assembled into linear chains using a biomolecular recognition system. In a direct relation with the present work, Clair et al [35] investigated the self-assembly of terephthalic acid (TPA) molecules on the Au(111) surface.…”
Section: Introductionmentioning
confidence: 99%
“…Such partial coating has been shown to favor assembly into side-by-side or end-to-end geometries, leading to superstructures with different degree of organization, complexity of collective behavior and unique optical properties. By taking advantage of interactions between small organic molecules [101] , polymers [102] , or biomolecules such as DNA [103] , oligonucleotides [104] or proteins (antibody -antigen [105] or biotin -strepavidin interactions [106] ), end-to-end and side-to-side assemblies of gold NRs have been successfully used for sensing applications [104,107] .…”
Section: Physically Adsorbed Polymersmentioning
confidence: 99%